2018
DOI: 10.1002/chem.201705842
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed C−S Bond Formation via Decarbonylative Thioetherification of Esters, Amides and Intramolecular Recombination Fragment Coupling of Thioesters

Abstract: A nickel catalyzed cross-coupling protocol for the straightforward C-S bond formation has been developed. Various mercaptans and a wide range of ester and amide substrates bearing various substituents were tolerated in this process which afforded products in good to excellent yields. Furthermore, an intramolecular protocol for the synthesis of thioethers starting from thioesters has been developed. The utility of this protocol has been demonstrated in a new synthetic protocol of benzothiophene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 87 publications
1
47
0
Order By: Relevance
“…As shown in Scheme , in 2019, Wang and Mei described a nickel‐catalyzed Ullmann‐type thiolation of aryl halides under mild electrochemical conditions respectively (Scheme a) . Rueping et al reported nickel‐catalyzed C−S bond formation via decarbonylative thioetherification of esters in 2018 (Scheme b) . In the same year, Szostak also developed a similar decarbonylative thioetherification by nickel catalyst (Scheme c) .…”
Section: Introductionsupporting
confidence: 91%
“…As shown in Scheme , in 2019, Wang and Mei described a nickel‐catalyzed Ullmann‐type thiolation of aryl halides under mild electrochemical conditions respectively (Scheme a) . Rueping et al reported nickel‐catalyzed C−S bond formation via decarbonylative thioetherification of esters in 2018 (Scheme b) . In the same year, Szostak also developed a similar decarbonylative thioetherification by nickel catalyst (Scheme c) .…”
Section: Introductionsupporting
confidence: 91%
“…Control studies revealed that both the nickel catalyst and zinc powder were essential elements (entries 12–13). The reaction failed completely when Zn was replaced by manganese, [13c] or other weak reducing agents [17] (e.g., ascorbic acid or polymethylhydrosiloxane (PMHS); entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…Rueping and co-workersr eported an air-and moisturestable nickel-catalyzed decarbonylative thioetherification of amides or esters through amide NÀCa ctivation (Scheme 38). [76] To avoid the use of moisture-and air-sensitive catalysts,t hat is, [Ni(cod) 2 ], the authors used an inexpensive ands table NiCl 2 catalyst. In addition, an improvement in the yield was observed when phosphine-based ligands wereu sed.…”
Section: Cross-coupling and Other Reactionsmentioning
confidence: 99%